DERIVATIONAL AND INFLECTIONAL MORPHEME ANALYSIS ON THE SONG LYRICS OF LADY GAGA “A STAR IS BORN” ALBUM - Ira Nur Aprianti; Aseptiana Parmawati (PROJECT (Professional Journal of English Education), 2020)
The tittle of this research is Affixes Analysis on the Song Lyrics of Lady Gaga “A Star is Born” Album. The method that used in this study is to analyst the lyrics of “A Star is Born” album and the technique that used to collect the data is analyzing technique that used is qualitative method. The purpose of this research is to identify and find out the farms of the affix of derivation and inflectional from the lyrics of “A Star is Born” album. Based on the analysis, it was found that many types of derivation and inflectional affix. The most dominant that found in the Lady Gaga album song is derivation affix. The result of this research, 14 data or 58,3% derivation affixes 10 data or 41,7%% that inflectional found in "A Stars is Born” album. Keywords:  Morphology, Affixes, Derivational, Inflectional